2005
DOI: 10.1021/bp050194s
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Amino Acids on Acrylamide Formation and Elimination Kinetics

Abstract: The effect of amino acids other than asparagine on acrylamide (AA) formation/elimination kinetics was studied in an asparagine-glucose model system (0.01 M, pH 6) heated at temperatures between 140 and 200 degrees C. Addition of cysteine or lysine to the model significantly lowered the AA yield, whereas addition of glutamine had a strong promoting effect and of alanine a rather neutral effect on the AA formation. This was also reflected by AA formation/elimination kinetics, which for all model systems studied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
87
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(97 citation statements)
references
References 25 publications
9
87
1
Order By: Relevance
“…The addition of glycine or glutamine during blanching of potato chips reduced the amount of acrylamide by almost 30% compared to control (Claeys et al, 2005). Acrylamide formation can be reduced significantly as well by introducing other amino acids, such as cysteine, lysine, or glycine, which would compete with asparagine for the carbonyl compounds in the Maillard reaction and/or enhance acrylamide elimination (Claeys et al, 2005). The nucleophilic sulphur atom of L-cysteine and the amino groups of the other amino acids might readily give rise to Michael type addition reactions with acrylamide (Fennell et al, 2005;Stadler et al, 2004).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The addition of glycine or glutamine during blanching of potato chips reduced the amount of acrylamide by almost 30% compared to control (Claeys et al, 2005). Acrylamide formation can be reduced significantly as well by introducing other amino acids, such as cysteine, lysine, or glycine, which would compete with asparagine for the carbonyl compounds in the Maillard reaction and/or enhance acrylamide elimination (Claeys et al, 2005). The nucleophilic sulphur atom of L-cysteine and the amino groups of the other amino acids might readily give rise to Michael type addition reactions with acrylamide (Fennell et al, 2005;Stadler et al, 2004).…”
Section: Discussionmentioning
confidence: 95%
“…Some authors diminished acrylamide formation in fried snacks products by adding amino acids, such as lysine, glycine and cysteine (Kim et al, 2005). The addition of glycine or glutamine during blanching of potato chips reduced the amount of acrylamide by almost 30% compared to control (Claeys et al, 2005). Acrylamide formation can be reduced significantly as well by introducing other amino acids, such as cysteine, lysine, or glycine, which would compete with asparagine for the carbonyl compounds in the Maillard reaction and/or enhance acrylamide elimination (Claeys et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The addition of the free amino acids glycine and L-lysine to the potato powder model system lowered the final acrylamide content, while keeping the pH at its original level. It was suggested that these components would reduce acrylamide formation by promoting competitive reactions and/or by covalently binding the formed acrylamide through Michael type addition reactions (Claeys, De Vleeschouwer, & Hendrickx, 2005;Kim, Hwang, & Lee, 2005;Low et al, 2006). Furthermore, organic acids, such as citric, acetic and Llactic acid reduced the final acrylamide content, but merely due to a reduced pH (Mestdagh et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…It was suggested that acetic acid would be a better acidulant for the pre-treatment of potato crisps compared to citric acid, due to the less appearing sourness (Kita et al, 2004). Addition of (sulphur containing) amino acids may also generate unpleasant off-flavours upon heating, which should be taken into account as well (Claeys et al, 2005). Calcium chloride might improve product texture, but on the other hand can cause a bitter aftertaste (Varela, Salvador, & Fiszman, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…It was also reported that the addition of certain amino acids other than asparagine reduces acrylamide levels in an aqueous system (Kim et al, 2005). Claeys et al (2005) kinetically analyzed the effect of amino acids on acrylamide formation/ elimination by heating a mixture of asparagine and glucose at temperatures between 140 and 200℃, and reported that the presence of cysteine or lysine significantly reduced acrylamide formation, whereas glutamine promoted the formation of acrylamide. There are also several studies reporting the reaction of acrylamide with amino acids such as glycine, lysine and cysteine at high temperatures (Adams et al, 2010;Liu et al, 2011;Zamora et al, 2010;Hidalgo et al, 2011).…”
Section: Introductionmentioning
confidence: 99%